Pressure Measurement Techniques for Abdominal Hypertension: Conclusions from an Experimental Model - Sascha Santosh Chopra; Stefan Wolf; Veit Rohde; Florian Baptist Freimann (Critical Care Research and Practice)
Introduction. Intra-abdominal pressure (IAP) measurement is an indispensable tool for the diagnosis of abdominal hypertension. Different techniques have been described in the literature and applied in the clinical setting. Methods. A porcine model was created to simulate an abdominal compartment syndrome ranging from baseline IAP to 30 mmHg. Three different measurement techniques were applied, comprising telemetric piezoresistive probes at two different sites (epigastric and pelvic) for direct pressure measurement and intragastric and intravesical probes for indirect measurement. Results. The mean difference between the invasive IAP measurements using telemetric pressure probes and the IVP measurements was −0.58 mmHg. The bias between the invasive IAP measurements and the IGP measurements was 3.8 mmHg. Compared to the realistic results of the intraperitoneal and intravesical measurements, the intragastric data showed a strong tendency towards decreased values. The hydrostatic character of the IAP was eliminated at high-pressure levels. Conclusion. We conclude that intragastric pressure measurement is potentially hazardous and might lead to inaccurately low intra-abdominal pressure values. This may result in missed diagnosis of elevated abdominal pressure or even ACS. The intravesical measurements showed the most accurate values during baseline pressure and both high-pressure plateaus.